THE ROLE OF NEUROPSYCHOLOGY IN DIAGNOSTICS AND TREATMENT OF PATIENTS WITH EPILEPSY: A REVIEW ARTICLE - Malobabić, Marina (Acta medicae Medianae, 2025)
Epilepsy represents a neurological disease with a prevalence of approximately 1% of the world population. Besides unprovoked seizures which are the main characteristic of this disease, there can be a decline in cognitive functioning, including memory and concentration dysfunctions, executive dysfunction, and visuoconstructional and visuospatial dysfunctions. However, behavioral changes can also be seen throughout the disease duration and/or during postoperative treatment of drug-resistant epilepsy. This article aims to emphasize that neuropsychological diagnostics and neuropsychology as a science are making a valuable contribution to the diagnostic process and can be used as a tool for examining the localization and/or lateralization of brain damage, determining the severity of cognitive deficits, monitoring disease and treatment, which improves quality and safety of treatment, as well as further detection of neuropsychological comorbidities and their rehabilitation.